Extrapyramidalism in Alzheimer's disease: prevalence, psychiatric, and neuropsychological correlates. Issue 12 (December 1994) - Merello, M; Sabe, L; Teson, A; Migliorelli, R; Petracchi, M; Leiguarda, R; Starkstein, S
Abstract : The prevalence and clinical correlates of extrapyramidal signs in a consecutive series of 78 patients with Alzheimer's disease attending a neurology clinic, and 20 age comparable normal controls, were examined. Based on the unified Parkinson's disease rating scale (UPDRS) findings, 18 patients (23%) met criteria for parkinsonism, 44 (56%) had isolated extrapyramidal signs, and 16 (21%) had no extrapyramidal signs. Whereas the control group showed a similar prevalence of isolated extrapyramidal signs (57%), none of them showed parkinsonism. No significant differences were found for age, sex, duration of illness, and severity of dementia among the three Alzheimer's disease groups. Patients with Alzheimer's disease-parkinsonism, however, showed a significantly higher frequency of major depression and dysthymia and significantly higher Hamilton depression scores than patients with isolated or no extrapyramidal signs. Patients with Alzheimer's disease-parkinsonism also showed significantly more deficits on frontal lobe related tasks such as the Wisconsin card sorting test, trail making test, and verbal fluency, as well as on tests of constructional praxis and abstract reasoning than patients with Alzheimer's disease but no extrapyramidal signs. In conclusion, the study showed a specific association between Alzheimer's disease and parkinsonism, as well as significant relations between parkinsonism, deficits in executive functions, and depression among patients with Alzheimer's disease.